2011
DOI: 10.1007/s10072-011-0701-6
|View full text |Cite
|
Sign up to set email alerts
|

Expression of dopamine 2 receptor subtype mRNA in clinically nonfunctioning pituitary adenomas

Abstract: Dopamine receptor agonists (DAs) can reduce hormone release and tumor mass in the majority of prolactinomas, whereas such effects are controversial in clinically nonfunctioning pituitary adenomas (NFPAs). Whether expression of dopamine 2 receptor (D2R) is different in subgroups of NFPAs has not been fully elucidated. We assessed and compared D2R subtype (long: D2L and short: D2S) mRNA levels in subgroups of NFPAs by real-time reverse transcriptase polymerase chain reaction (RT-PCR). For both D2L and D2S mRNA, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
11
0
1

Year Published

2011
2011
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(12 citation statements)
references
References 23 publications
0
11
0
1
Order By: Relevance
“…compared the DR2 mRNA content (TaqMan ® ) between 63 gonadotroph and six null‐cell adenoma and did not find a significant difference. Similarly, Su et al . showed that DR2 mRNA expression (TaqMan ® ) was not different between 25 gonadotropinomas and 21 null‐cell adenomas.…”
Section: Discussionmentioning
confidence: 90%
“…compared the DR2 mRNA content (TaqMan ® ) between 63 gonadotroph and six null‐cell adenoma and did not find a significant difference. Similarly, Su et al . showed that DR2 mRNA expression (TaqMan ® ) was not different between 25 gonadotropinomas and 21 null‐cell adenomas.…”
Section: Discussionmentioning
confidence: 90%
“…Thus, dopamine agonists (DA) reduce gonadotropin secretion (14) and inhibit thymidine incorporation in vitro (15), providing a potential therapeutic target for NFPA. However, dopaminergic binding sites (16) as well as D2R mRNA isoforms (17) are less abundant in NFPA than in prolactinomas, perhaps accounting for the modest rate of tumor shrinkage attained by DAs (18). Small studies, including a report from our own group (19), suggested that DA may retard NFPA growth (20,21,22,23,24), but to date, this potential therapeutic modality has not been broadly practiced.…”
Section: Introductionmentioning
confidence: 99%
“…Older small series and case reports suggested that DA can induce tumor shrinkage in NFPA, [43,44], but the effects were lesser than those seen in prolactinomas, possibly reflecting the lower expression of dopamine receptors [45]. We have introduced the concept that in the absence of mass effects, the treatment goal for NFPA should be tumor stabilization and growth prevention, not tumor shrinkage [46].…”
Section: Medical Treatmentmentioning
confidence: 97%